КРИМІНАЛЬНО-ПРАВОВА ХАРАКТЕРИСТИКА ВІЙСЬКОВИХ ЗЛОЧИНІВ - Бершов, Геннадій Євгенович (SUPREMANCE OF LAW, 2018)
The article emphasizes that, despite the fact that military crimes are a criminal legal category, their characteristics are regulated along with criminal legislation by a number of normative legal acts that determine the legal basis of military service and the procedure for its completion. It is noted that, when carrying out a criminal-legal characterization of the elements of war crimes, it is necessary to take into account the blanket nature of the norms of criminal legislation. It has been established that the procedure for completing military service can be somewhat refined and differ depending on the type of military service, which means that the mandatory and optional elements of the composition of certain types of military crimes will also be slightly different.
Keywords: war crimes; criminal-legal characteristics; composition of a criminal offense; object; objective side; subject; subjective side